The effect of aromatherapy with Lavender-Neroli oil and music in management of pediatric dental anxiety: a randomized control trial - Rama Abdalhai; Chaza Kouchaji; Rasha Alkhatib (Nature Publishing Group, 2024)
Abstract Aim This study aimed to evaluate the efficacy of aromatherapy with Lavender-Neroli essential oil combined with background music in reducing dental anxiety and pain during anesthesia in children. Materials and methods A total of 56 children aged 6-10 years old who needed dental treatment with inferior alveolar nerve injection (IANB) were randomly divided into two groups: Group 1 (Experimental, n = 28) aromatherapy with music group, and Group 2 (Control, n = 28) the placebo group. Children in the group 1 were asked to inhale the aromatic blend of Lavender-Neroli essential oil using a nasal mask similar to one that is used for nitrous oxide after modifying it by adding a 3D printed box on its circle hole and listening to their favorite music as a background before 5 min and during anesthesia, meanwhile in the placebo group children were asked to wear an empty nasal mask. Anxiety and pain were been assessed before and after anesthesia using the self-report anxiety scale Facial image scale (FIS), Observational pain assessment scale Face-Legs-Activity-Cry-Consolability (FLACC), heart rate, SPO2 saturation, diastolic and systolic blood pressure. Results Dental anxiety and vital signs except SPO2 saturation were significantly lower in the aromatherapy with music group when compared to the control group (p < 0.05), with no differences in pain perception between groups (p = 0.176). Conclusions Aromatherapy with Lavender-Neroli oil combined with music seems to be a useful and safe non-pharmacologic technique for managing dental anxiety in children.